2020
DOI: 10.21873/invivo.11811
|View full text |Cite
|
Sign up to set email alerts
|

Butyric Acid in Saliva of Chronic Periodontitis Patients Induces Transcription of the EBV Lytic Switch Activator BZLF1: A Pilot Study

Abstract: Background/Aim: Epstein-Barr virus (EBV) associates with human chronic periodontitis (CP) progression. We previously demonstrated that butyric acid (BA), produced by periodontopathic bacteria, induced EBV lytic switch activator BZLF1 expression. We investigated whether short chain fatty acids (SCFAs) in CP patients' saliva enabled EBV reactivation. Materials and Methods: Saliva was collected from seven CP patients and five periodontally healthy individuals. SCFAs were quantified using HPLC. BZLF1 mRNA and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…It has been reported that more than adequate concentrations of BA for gene activation were present in the dental plaques (range = 4.7–13.8 mM) and periodontal pockets (mean, 2.6 ± 0.4 mM) of patients with periodontal disease [ 48 , 49 ], whereas BA concentration was below the detection limits in healthy sites [ 50 ]. We also previously reported that high concentrations (millimolar levels) of BA are present in the saliva of Japanese patients with periodontal disease, and a significant correlation between BA concentrations and BZLF1 transcript levels was noted [ 51 ]. These observations and our findings suggest that BA produced by F. nucleatum in the saliva of patients with periodontal disease might be involved in the upregulation of ACE2 and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than adequate concentrations of BA for gene activation were present in the dental plaques (range = 4.7–13.8 mM) and periodontal pockets (mean, 2.6 ± 0.4 mM) of patients with periodontal disease [ 48 , 49 ], whereas BA concentration was below the detection limits in healthy sites [ 50 ]. We also previously reported that high concentrations (millimolar levels) of BA are present in the saliva of Japanese patients with periodontal disease, and a significant correlation between BA concentrations and BZLF1 transcript levels was noted [ 51 ]. These observations and our findings suggest that BA produced by F. nucleatum in the saliva of patients with periodontal disease might be involved in the upregulation of ACE2 and proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…EBV exhibits latent and lytic phases that establish a persistent infection in the host. Several bacteria, such as Porphyromonas gingivalis and Fusobacterium nucleatum , have been associated with periodontitis [ 4 , 53 ]. Kato et al [ 8 , 9 ] found greater coexistence of OR EBV DNA with P .…”
Section: Discussionmentioning
confidence: 99%
“…nucleatum produce high levels of butyric acid [ 54 ], and a recent study showed that the saliva of chronic periodontitis patients contains butyric acid at higher levels than in healthy controls [ 55 ]. Butyric acid may play a role in the initiation of EBV reactivation and contribute to the clinical progression of patients with periodontal disease by inducing lytic switch activator BZLF1 expression in EBV [ 53 ]. The immediate-early BZLF1 gene encodes ZEBRA, which induces the lytic replication cycle in latently infected B cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chromatin immunoprecipitation assays have revealed the dissociation of HDAC1, 2, and 7 from the BZLF1 promoter after EBV-infected B cells were treated with conditioned media derived from the cultures of the periodontopathic bacteria [ 191 ]. Moreover, high concentrations of butyric acid are present in the periodontal pockets and saliva [ 192 , 193 ]. Butyric acid is also a known potent activator of the HIV lytic cycle [ 194 ].…”
Section: Ebv Interactions With Oral Bacteria May Facilitate Viral Transmission and Promote Periodontal Diseasesmentioning
confidence: 99%